Լեռնային Ղարաբաղի Ինքնավար Մարզի մշակույթի պատմության վերաիմաստավորումը Արցախի պաշտպանության բանակի ազատագրական առաքելության համատեքստում - Հարությունյան Մհեր / Harutyunyan Mher (Հայաստանի ազգային գրադարան / National Library of Armenia, 2024)
Resisting the aggression of the Azerbaijani Armed Forces and pursuing the enemy fleeing from the battlefield, the Artsakh Self-Defence Forces in 1991-1994 liberated the territories of the historical Syunik, Artsakh and Utik provinces, which had been illegally annexed to Soviet Azerbaijan. The latter, continuing the Turkish policy of Armenocide in Transcaucasia, depatriated the autochthonous Armenian population by criminal methods of massacres, ethnic cleansing and forced religious conversion, mercilessly destroyed or usurped in the occupied settlements the centuries-old heritage of Armenian culture, which for centuries had served to preserve the national identity of the autochthonous Armenian population of Artsakh. The purpose of reinterpreting the cultural heritage of the Soviet period is to emphasise the urgency of liberating historical Artsakh based on Armenia's defence, security and military-political priorities and the need for the immediate return of the Armenian population in one of the most important territories of Armenian culture.
Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2024 ․- N 1 .- էջ 34-44
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն